Examining the effects of a targeted noise reduction program in a neonatal intensive care unit. Issue 3 (19th December 2013) - Wang, D; Aubertin, C; Barrowman, N; Moreau, K; Dunn, S; Harrold, J
Abstract : Objectives: To determine whether implementation of a noise reduction policy followed by the addition of direct audit and feedback reduces noise levels in a tertiary-level neonatal intensive care unit (NICU). Study design: Noise level data was collected in three phases: (1) baseline (preintervention), (2) immediately postimplementation of our noise reduction policy, (3) postunveiling of direct audit and feedback mechanism. Setting: A level 3 NICU in Ontario, Canada. Interventions: Noise reduction policy and a direct audit and feedback mechanism. Main outcome measures: Average noise level. Results: The baseline level of noise in our unit consistently exceeds guidelines with an average baseline noise of 49 dB (±1.4). Our intervention resulted in a significant reduction in noise levels for one of the four areas in our NICU [−1.06 dB (−1.52, −0.6)], with a trend towards reduction in a second area (−0.21 dB (−0.6, 0.18)). Unexpectedly, two other areas experienced a significant increase in noise (2.05 dB (1.18, 2.94); 0.85 dB (0.11, 1.59)). Conclusions: The baseline noise in the NICU consistently exceeds guidelines, but reductions in noise levels are achievable. Nonetheless, more work is needed to find the optimal NICU design and noise reduction strategy.